2012
DOI: 10.1177/0884533612448479
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge of Developing a New Predictive Formula to Estimate Energy Requirements in Ventilated Critically Ill Children

Abstract: All 3 new pediatric intensive care unit equations have R² values of > 0.8; however, the Schofield equation still performed better than other predictive methods in predicting energy expenditure in these patients. Still, none of the predictive equations, including the new equations, predicted energy expenditure within a clinically accepted range, and further research is required, particularly for patients outside the technical scope of indirect calorimetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 46 publications
3
53
0
3
Order By: Relevance
“…Those developed to estimate energy expenditure in healthy children and extrapolated to use in the critically ill have been reported to be inaccurate in different populations, and their detailed review is out of the scope of this manuscript (6, 6467). However, two equations have been derived for use in critically ill children: White and Meyer (68, 69). A recent validation study compared energy expenditure predicted by those two equations to measured energy expenditure by indirect calorimetry in a patient population similar to the one the equations were derived from and found errors of −20 to +50% in both (70).…”
Section: Introductionmentioning
confidence: 99%
“…Those developed to estimate energy expenditure in healthy children and extrapolated to use in the critically ill have been reported to be inaccurate in different populations, and their detailed review is out of the scope of this manuscript (6, 6467). However, two equations have been derived for use in critically ill children: White and Meyer (68, 69). A recent validation study compared energy expenditure predicted by those two equations to measured energy expenditure by indirect calorimetry in a patient population similar to the one the equations were derived from and found errors of −20 to +50% in both (70).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent work has suggested that PEE equations fail to adequately predict REE. New paediatric intensive care unit (PICU)-oriented equations have been found to be no better than well-established tools, such as the Schofield-HW equation [2]. We have compared PICU-specialized and commonly used PEE equations with REE using a new modular metabolic monitor (E-COVX) in well-nourished and malnourished critically ill children.…”
mentioning
confidence: 99%
“…The nutritional status was evaluated for the presence of proteinenergy malnutrition as defined by Waterlow [5]. The PEE was estimated and basal metabolic rate (PBMR) was predicted using the common Harris-Benedict, Schofield-HW, Seashore, Fleisch, CaldwellKennedy and Henrys formulas, as well as equations specifically developed for the PICU by White and by Meyer [2]. Patients were classified as hypermetabolic, normometabolic and hypometabolic when the REE was [110, 90-110 and \90 % of the Schofield-PBMR, respectively, and as overfed, adequately fed and underfed when the caloric intake was [110, 80-110 and \80 % of the REE, respectively.…”
mentioning
confidence: 99%
“…It has also been demonstrated that early on in critical illness, a lower body metabolic rate is present. The REE calculated from predictive formulas does not need to be met fully on day 1 of the critical illness [48].…”
Section: Estimating Energy Needsmentioning
confidence: 99%